Ambient intelligence : software and applications -- 8th International Symposium on Ambient Intelligence (ISAmI 2017) - Paz Santana, Juan F. de; Julian, Vicente; Villarrubia, Gabriel; Marreiros, Goreti; Novais, Paulo (Springer, 2017)
Ambient Intelligence (AmI) is a recent paradigm emerging from Artificial Intelligence, in which computers are used as proactive tools to assist people with their day-to-day activities, making their lives more comfortable. Another main goal of AmI originates from the human/computer interaction domain and focuses on offering ways to interact with systems in a more natural way by means of user-friendly interfaces. This field is evolving quickly, as can be witnessed by the emerging natural-language-based and gesture-based types of interaction. The inclusion of computational power and communication technologies in everyday objects is growing, and their embeddedness in our environments should be as invisible as possible. In order for AmI to be successful, human interaction with computing power and embedded systems in the surroundings should be smooth and take place without people actually noticing it. The only things people should notice in connection with AmI are more safety, comfort and wellbeing, emerging in a natural and inherent way. ISAmI is the International Symposium on Ambient Intelligence and aims to bring together researchers from the various disciplines that constitute the scientific field of Ambient Intelligence to present and discuss the latest results, new ideas, projects and lessons learned, especially in terms of software and applications.
Keywords: Ambient intelligence -- Congresses.; elektronické knihy; electronic books